Bacillus benefits the competitive growth of Ambrosia artemisiifolia by increasing available nutrient levels - Zhang, Fengjuan; Sun, Jianru; Wang, Chang; Li, Chunying; Chen, Fengxin; Xu, Haiyun; Chen, Xue (Frontiers in Plant Science, 2023)
Bacillus can help plants to acquire nutrients either directly or indirectly. However, the role of Bacillus community on the competitive growth of invasive Ambrosia artemisiifolia is poorly understood. Native S. viridis is often found in areas that have been invaded by A. artemisiifolia. We sought to determine whether the quantitative and/or qualitative differences in the Bacillus community present on the invasive Ambrosia artemisiifolia and native Setaria viridis provide a competitive advantage to the invasive over native species. A field experiment was established to imitate the invasion of A. artemisiifolia. The 16S rRNA gene was commercially sequenced to identify the bacilli isolated from the rhizosphere soil of field-grown A. artemisiifolia and S. viridis. The Bacillus communities in their rhizosphere were compared, and their effects on the competitive growth of A. artemisiifolia and S. viridis were tested in the pot experiments. Bacillus in the rhizosphere soil of A. artemisiifolia significantly enhanced its intra-specific competitive ability. The relative abundance of B. megaterium in the rhizosphere soil of A. artemisiifolia was significantly higher than that of S. viridis. Inoculation with B. megaterium that was isolated from the rhizosphere soil of both A. artemisiifolia and S. viridis significantly enhanced the relative competitiveness of A. artemisiifolia and inhibited that of S. viridis. The higher abundance of B. megaterium in the rhizosphere of A. artemisiifolia creates higher levels of available nutrients than that in the native S. viridis, which enhance the competitive growth of A. artemisiifolia.